"Recalling-ls-Greatest": Personal Memory and Lyricism in Toyin Falola's A Mouth Sweeter than Salt and Counting the Tiger's Teeth - Felicia Ohwovoriole (Yoruba Studies Review)
The reflective disclosure of the past is a major trend in African literature as indicated in writers like Wale Soyinka, Chinua Achebe and Ngugi Wa Thiong'o. Personal memory is also often employed aesthetically to mirror what is embedded in the past. Toyin Faiola the author of A Mouth Sweeter than Salt and Counting the Tiger's Teeth presents his childhood and teenage years, family history and the social and historical events of Ibadan, Ilorin and Ile-Ife, Nigeria. He also details his personal experiences as a witness to the Agbekoya rebellion of 1968-70. In presenting actions in the two self-narratives, Toyin Faiola exploits the resources of indigenous and contemporary African songs, incantatory chants and transliterated version of many lyrics. He uses the lyrics to also investigate the symbolic meaning of words used in the past and reiterates the prevalence of songs in Yoruba culture. The lyrics link together many themes as well as serving as an avenue for community and individual expression. We have memorial songs, songs of rebellion, songs of sexuality and satirical songs which mock teachers, the police and government officials. Faiola presents an inseparable relationship of mutual exchange between the oral and written traditions. However, our point of emphasis is to evaluate the context and usage of the lyrics and panegyrics in the two texts.